2007
DOI: 10.1259/bjr/24766640
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of doses from ionizing radiation using fluorescencein situhybridization techniques

Abstract: This paper reviews cytogenetic methods of biological dosimetry. The most reliable indicator of exposure to ionizing radiation is the observation of dicentrics in human peripheral lymphocytes. The major disadvantage is that dicentrics cannot be used for exposures that occur many years prior to blood sampling. In such cases, translocations are the aberrations of choice, and recent developments in their measurement using fluorescence in situ hybridization techniques are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Chromosome changes also play a major role in carcinogenesis (2) and there is increasing evidence that their presence in peripheral blood lymphocytes provides a marker of cancer risk (3). For the assessment of historical and chronic exposures to ionizing radiation the translocation is the aberration of choice (1,(4)(5)(6). Translocations are stable aberrations that persist through cell division and their presence in peripheral blood lymphocytes is maintained because descendants of irradiated bone marrow stem cells carrying translocations survive and appear in the circulating blood.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome changes also play a major role in carcinogenesis (2) and there is increasing evidence that their presence in peripheral blood lymphocytes provides a marker of cancer risk (3). For the assessment of historical and chronic exposures to ionizing radiation the translocation is the aberration of choice (1,(4)(5)(6). Translocations are stable aberrations that persist through cell division and their presence in peripheral blood lymphocytes is maintained because descendants of irradiated bone marrow stem cells carrying translocations survive and appear in the circulating blood.…”
Section: Introductionmentioning
confidence: 99%
“…SEER cancer database data 49 on age dependence of background CML incidence; and, for comparison, data on age dependence of background chromosome translocations developed to assist radiation biodosimetry (reviewed in Edwards et al 50 and Sigurdson et al 51 ).…”
Section: Data Consideredmentioning
confidence: 99%
“…Quantitative models that analyze CML treatment have not yet incorporated analyses of CML incidence with age. This section discusses results, relevant to any such unification, on how background in vivo chromosome translocation levels increase with age.The translocation data presented in Figure 5 were generated as controls for radiation biodosimetry (reviewed in Edwards et al, 50 Sigurdson et al, 51 and Tucker 52 ) and do not single out BCR-ABL. In these data, accumulated numbers of clones with translocations are counted at various ages; a clone with a specific translocation is counted only once no matter how many cells the clone has.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus for protracted low-LET exposure, translocation frequencies should increase with cumulative dose and provide a good measure of total dose. Indeed it has been suggested that the main application for FISH translocation analysis is in assessing long-term low-dose-rate cumulative exposure and thus, it is a useful tool in dose reconstruction for epidemiological studies (5).…”
Section: Introductionmentioning
confidence: 99%